Re-evaluation of the cardioprotective effects of cannabinoids against ischemia-reperfusion injury according to the IMproving Preclinical Assessment of Cardioprotective Therapies (IMPACT) criteria - Pędzińska-Betiuk, Anna; Schlicker, Eberhard; Weresa, Jolanta; Malinowska, Barbara (Frontiers in Pharmacology, 2024)
Ischemic heart disease, associated with high morbidity and mortality, represents a major challenge for the development of drug-based strategies to improve its prognosis. Results of pre-clinical studies suggest that agonists of cannabinoid CB2 receptors and multitarget cannabidiol might be potential cardioprotective strategies against ischemia-reperfusion injury. The aim of our study was to re-evaluate the cardioprotective effects of cannabinoids against ischemia-reperfusion injury according to the IMproving Preclinical Assessment of Cardioprotective Therapies (IMPACT) criteria published recently by the European Union (EU) CARDIOPROTECTION COST ACTION. To meet the minimum criteria of those guidelines, experiments should be performed (i) on healthy small animals subjected to ischemia with reperfusion lasting for at least two hours and (ii) confirmed in small animals with comorbidities and co-medications and (iii) in large animals. Our analysis revealed that the publications regarding cardioprotective effects of CB2 receptor agonists and cannabidiol did not meet all three strict steps of IMPACT. Thus, additional experiments are needed to confirm the cardioprotective activities of (endo)cannabinoids mainly on small animals with comorbidities and on large animals. Moreover, our publication underlines the significance of the IMPACT criteria for a proper planning of preclinical experiments regarding cardiac ischemia-reperfusion injury.